IL‐35 recombinant protein reverses inflammatory bowel disease and psoriasis through regulation of inflammatory cytokines and immune cells. Issue 2 (29th November 2017) - Wang, Yuan; Mao, Ying; Zhang, Junfeng; Shi, Gang; Cheng, Lin; Lin, Yi; Li, Yiming; Zhang, Xiaomei; Zhang, Yujing; Chen, Xiaolei; Deng, Jie; Su, Xiaolan; et al.
Abstract: Interleukin‐35 (IL‐35), a member of the IL‐12 family, functions as a new anti‐inflammatory factor involved in arthritis, psoriasis, inflammatory bowel disease (IBD) and other immune diseases. Although IL‐35 can significantly prevent the development of inflammation in many diseases, there have been no early studies accounting for the role of IL‐35 recombinant protein in IBD and psoriasis. In this study, we assessed the therapeutic potential of IL‐35 recombinant protein in three well‐known mouse models: the dextransulfate sodium (DSS)‐induced colitis mouse model, the keratin14 (K14)‐vascular endothelial growth factor A (VEGF‐A)‐transgenic (Tg) psoriasis mouse model and the imiquimod (IMQ)‐induced psoriasis mouse model. Our results indicated that IL‐35 recombinant protein can slow down the pathologic process in DSS‐induced acute colitis mouse model by decreasing the infiltrations of macrophages, CD4 + T and CD8 + T cells and by promoting the infiltration of Treg cells. Further analysis demonstrated that IL‐35 recombinant protein may regulate inflammation through promoting the secretion of IL‐10 and inhibiting the expression of pro‐inflammatory cytokines such as IL‐6, TNF‐α and IL‐17 in acute colitis model. In addition, lower dose of IL‐35 recombinant protein could achieve long‐term treatment effects as TNF‐α monoclonal antibody did in the psoriasis mouse. In summary, the remarkable therapeutic effects of IL‐35 recombinant protein in acute colitis and psoriasis mouse models indicated that IL‐35 recombinant protein had a variety of anti‐inflammatory effects and was expected to become an effective candidate drug for the treatment of inflammatory diseases.